STUDY OF NATIONAL CURRICULUM IMPLEMENTATION IN INDONESIA AND AFRICA SOUTH: CHALLENGES AND SOLUTIONS IN IMPROVING THE QUALITY OF EDUCATION - Pajri, Ahmad Khairul; Agusti, Jeya; Purba, Grace; Koto, Irwan (MEDIA DIDAKTIKA, 2025)
Study This aiming For compare implementation curriculum national in Indonesia and South Africa, with focus on challenges and solutions in increase quality Education . Research This motivated by the need For understand How system different education​ handle issues general like adaptation curriculum , teacher competence , allocation source power , and results Study students . With use approach qualitative comparative , data collected through analysis documents , interviews with stakeholders interest education , and observation fields in both countries. Findings study disclose that although both countries face challenge similar , like gap in access and quality education , they implementing different strategies For overcome problem said . Indonesia emphasized teacher training and engagement society , while South Africa focuses on policy reform and development infrastructure . This study conclude that combination from approaches said , which is adjusted with context local , can in a way significant increase results Education . Research This give contribution to the discussion latest about implementation curriculum and offers recommendation practical for maker policies and educators in both countries.